2019
DOI: 10.1007/s00431-019-03330-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth impairment and limited range of joint motion in children should raise suspicion of an attenuated form of mucopolysaccharidosis: expert opinion

Abstract: Growth impairment together with bone and joint involvement is common to most patients with mucopolysaccharidosis (MPS) disorders. The genetic basis for these metabolic disorders involves various enzyme deficiencies responsible for the catabolism of glycosaminoglycans (GAGs). The incomplete degradation and subsequent accumulation of GAGs result in progressive tissue damage throughout the body. Bone ossification is particularly affected, with the consequent onset of dysostosis multiplex which is the underlying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…Other manifestations in the lower extremities include coxa valga and genu valgum. Joint symptoms, such as joint stiffness and limited range of joint mobility, stem from GAG accumulation and secondary pathogenic cascades in the ligaments and capsule around the joints [88,89].…”
Section: Skeletal Disease and Joint Symptoms In Mps Imentioning
confidence: 99%
“…Other manifestations in the lower extremities include coxa valga and genu valgum. Joint symptoms, such as joint stiffness and limited range of joint mobility, stem from GAG accumulation and secondary pathogenic cascades in the ligaments and capsule around the joints [88,89].…”
Section: Skeletal Disease and Joint Symptoms In Mps Imentioning
confidence: 99%
“…Abnormal growth is a frequent finding in MPS patients. In particular, in patients with MPS VI, normal growth is evident until 1.5 years of age and is then followed by growth stunting (−2 to −3 SD at 3.5 and 9 years, respectively) 21 . Clinical trials with ERT have shown a slight improvement in growth rate (height), which is not statistically significant when compared to patients who are not on treatment 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenge to correctly diagnose MPS IVA, especially in its attenuated form, because of the wide spectrum of clinical characteristics in patients with MPS IVA and because the radiographic findings are similar to those in patients with multiple epiphyseal dysplasia. Experts have presented a diagnostic algorithm based on the decline in growth velocity as well as bone and joint involvement that was designed to help paediatricians identify the early characteristics of the attenuated forms of MPS [ 13 ]. Once MPS is clinically suspected, urinary GAG analysis and enzyme detection are crucial for accurate diagnosis and prognosis of MPS subtypes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experts have presented a diagnostic algorithm based on the decline in growth velocity as well as bone and joint involvement that was designed to help paediatricians identify the early characteristics of the attenuated forms of MPS [ 13 ]. Once MPS is clinically suspected, urinary GAG analysis and enzyme detection are crucial for accurate diagnosis and prognosis of MPS subtypes [ 13 ]. However, the clinical features in patients with mild MPS are atypical, and mutation in other genes can lead to decreased GALNS activity such as multiple sulfatase deficiency, increasing the difficulty of diagnosing this disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%